2015
DOI: 10.3389/fimmu.2015.00579
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-Mediated Interactions in Thymocyte Migration and Development

Abstract: Intrathymic T-cell differentiation is a key process for the development and maintenance of cell-mediated immunity, and occurs concomitantly to highly regulated migratory events. We have proposed a multivectorial model for describing intrathymic thymocyte migration. One of the individual vectors comprises interactions mediated by laminins (LMs), a heterotrimeric protein family of the extracellular matrix. Several LMs are expressed in the thymus, being produced by microenvironmental cells, particularly thymic ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 127 publications
1
19
0
2
Order By: Relevance
“…However, it is a fact that laminins interact with several integrin isoforms and are involved in migration and development [35, 68]. Moreover, since the gene expression of LAMA1 was down-regulated in MCS cells, an impact of this gene or protein seems to be very likely.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is a fact that laminins interact with several integrin isoforms and are involved in migration and development [35, 68]. Moreover, since the gene expression of LAMA1 was down-regulated in MCS cells, an impact of this gene or protein seems to be very likely.…”
Section: Discussionmentioning
confidence: 99%
“…LNs are composed of three subunits, designated α, β and γ chains, which assemble into a cross-shaped trimer to form 16 different isoforms [6][7][8]. The most widely expressed LN subunit in adult basement membranes is the laminin-α5 chain (LN-α5) [9]. Unique developmental roles of LN-α5 have been studied in knockout (LN5-KO) mice since 1998, the result demonstrated embryos lacking LN-α5 die late in embryogenesis, and exhibit multiple developmental defects, including exencephaly, syndactyly and dysmorphogenesis of placental labyrinth.…”
Section: Introductionmentioning
confidence: 99%
“…8,20 In particular, others and we have demonstrated the expression of laminin isoforms in human and murine thymus, as well as the expression of functional laminin receptors by TEC and developing thymocytes, which play a role in the adhesion of thymocytes to TEC in normal murine and human thymuses. 21 CD49f is an ECM cell adhesive protein, a6 integrin chain, encoded by the ITGA6 gene, which can associate with b1 or b4 sub-unities to form laminin receptors. 22 In normal epithelial tissues, a6b4 has been implicated in forming and stabilizing of hemidesmosomes, which contribute to the organization and maintenance of epithelial structure.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Accordingly, thymocyte adhesion on microenvironmental cells, as well as thymocyte migration, is dependent on laminin-mediated interaction, through integrin-type receptors, such as VLA-6 (a6b1 or CD49f/CD29). 21,28 Recently, we showed that siRNA targeting ITGA6 in TEC could modulate cell migration-related genes, including those coding for ECM as well as chemokine ligands and receptors, promoting a significant decrease in cell adhesion to laminin. 28 In a second vein, the integrin b4 subunit is associated with proliferation of endothelial cells through a molecular association with HLA-ABC, which corresponds to class I molecules of the major histocompatibility complex.…”
Section: Introductionmentioning
confidence: 99%